LEGITIMATING INTERNET.ORG THROUGH DEVELOPMENT DISCOURSE - Alarcon, Andrea (AoIR Selected Papers of Internet Research, 2018)
This paper examines Mark Zuckerberg’s socio-technical optimistic imaginary of a connectivity of the entire world, focusing on Facebook’s Internet.org initiative. His vision of a connected world can be described as what Jasanoff and Kim (2015) call “sociotechnical imaginary,” which are not limited to nations, or heads of states, but can be conjured by corporations, social movements, and professional societies. The paper examines 50 short promotional videos, first-person narrated by individuals in their target countries. The themes found in the videos map to development discourse: female empowerment, education, entrepreneurship, and natural disaster relief. This paper argues that by merging Internet.org with connectivity, and connectivity with progress, Facebook utilizes the promotional aesthetic and narrative devices usually used by the development sector to position its initiative as a crucial step toward poverty alleviation and economic development.